2015
DOI: 10.1021/acs.est.5b02977
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of Sulfur Dioxide in Small Clusters of Sulfuric Acid: Mechanistic and Kinetic Study

Abstract: The deposition and hydrolysis reaction of SO2 + H2O in small clusters of sulfuric acid and water are studied by theoretical calculations of the molecular clusters SO2-(H2SO4)n-(H2O)m (m = 1,2; n = 1,2). Sulfuric acid exhibits a dramatic catalytic effect on the hydrolysis reaction of SO2 as it lowers the energy barrier by over 20 kcal/mol. The reaction with monohydrated sulfuric acid (SO2 + H2O + H2SO4 - H2O) has the lowest energy barrier of 3.83 kcal/mol, in which the cluster H2SO4-(H2O)2 forms initially at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
82
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(99 citation statements)
references
References 58 publications
17
82
0
Order By: Relevance
“…3,4,14 2-Butanethiol was detected in samples of air from sewerage treatment tanks of chemical petroleum, geothermal areas, muddy beach water and wastewater treatment plants. 2,[15][16][17][18] There are several experimental and theoretical studies of the reactions of alkyl thiols with Cl atoms and OH radicals. [19][20][21][22][23][24][25][26][27] In all cases the rates coefficients for Cl-atoms were an order of magnitude faster than the corresponding reaction with OH radical.…”
Section: Introductionmentioning
confidence: 99%
“…3,4,14 2-Butanethiol was detected in samples of air from sewerage treatment tanks of chemical petroleum, geothermal areas, muddy beach water and wastewater treatment plants. 2,[15][16][17][18] There are several experimental and theoretical studies of the reactions of alkyl thiols with Cl atoms and OH radicals. [19][20][21][22][23][24][25][26][27] In all cases the rates coefficients for Cl-atoms were an order of magnitude faster than the corresponding reaction with OH radical.…”
Section: Introductionmentioning
confidence: 99%
“…New models have been recently proposed for the formation of sulfate in the troposphere, clouds, aerosols, acid rain, and fog to bridge the gap between the modeled and observed sulfate. 20,[32][33][34][35] SO 2 can be quickly taken into fog and rain droplets, 36 which is followed by its liquid phase oxidation by O 3 and H 2 O 2 . 20,24,28,29,37,38 Model studies suggest that the oxidation of SO 2 in the aqueous phase results in more than 80% of the global sulfate production.…”
Section: Introductionmentioning
confidence: 99%
“…47 Recent studies have shown that SO 2 can hydrolyze to produce sulfurous acid (H 2 SO 3 ) or HSO 3 À in the gas phase in the presence of acid molecules or clusters such as water, hydrated ammonia, and hydrated sulfuric acid clusters. 33,34 In addition, sulfurous acid and bisulte were thought to be potential precursors for the formation of atmospheric aerosols. However, to the best of our knowledge, no studies have been reported on the atmospheric oxidation of H 2 SO 3 /HSO 3 À to produce H 2 SO 4 /HSO 4 À .…”
mentioning
confidence: 99%
“…The second method is quantum chemical calculations which can be used to obtain equilibrium structures, energies and thermochemical parameters, and for which results for a number of small clusters in the atmosphere have been reported. These theoretical studies include equilibrium structures, [35][36][37][38][39][40][41] transition states, 44,45 formation energies 36,37,[46][47][48][49][50][51] and nucleation rates. 58,59 However, quantum chemical calculations on nanosize clusters have been somewhat limited.…”
Section: Introductionmentioning
confidence: 99%